Social Media, Cyber Hate, and Racism - Khoirul Amin; Mohamad Dziqie Aulia Alfarauqi; Khusnul Khatimah (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2018)
In the era of information technology, the power of social media such as Facebook, Twitter, Instagram and other products of digital technology have led to dramatic changes to the social life of people in a pluralistic Indonesia. The establishment of a digital public space that can accommodate all entities, classes, or social communities to communicate freely, without limit and open up greater opportunities for the achievement of goals in accordance with the interests, both on the basis of political goals, economic, cultural, trust and ethnic , also helped to increase the potential for social conflicts with more complex backgrounds. One of them is the widespread of racism in social media against ethnic of minorities as it occurred during the 2017 Jakarta governor election involving Basuki Tjahaya Purnama, a candidate of the ethnic of Chinese-Indonesian. This paper seeks to explore the contribution of social media as a medium for spreading the hate of speech and racism and the factors that cause it. This article finds that; firstly, the development of information technology and freedom gained by every user in managing social media member space for racism group in Indonesia utilizes the progress of information technology as medium in spreading hatred and racism in Cyber space. Secondly, the existence of hate speech and racism in social media cannot be separated from socio-political situation in society.